2019
DOI: 10.1039/c9sc00693a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen deficiency on the excited state kinetics of WO3 and implications for photocatalysis

Abstract: Using WO3 as a model material, we investigate how different oxygen vacancy concentrations affect trapping of photogenerated charges and photocatalytic reactions in metal oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
142
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 67 publications
(81 reference statements)
19
142
0
Order By: Relevance
“…This latter assignment stems from two previous observations. Firstly, outside the SCL (or in the absence of one), photogenerated holes rapidly trap into occupied oxygen vacancy states, resulting in a bleached signal over the W 5+ absorption range, 17 consistent with the rapid initial decay at 700 nm in Figure 2a indicative of a loss of electron absorption. Secondly, catalytically active holes that absorb at 500 nm have been shown to oxidise water on slower timescales, thereby indicating that this absorption arises from holes localised within the depletion layer.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…This latter assignment stems from two previous observations. Firstly, outside the SCL (or in the absence of one), photogenerated holes rapidly trap into occupied oxygen vacancy states, resulting in a bleached signal over the W 5+ absorption range, 17 consistent with the rapid initial decay at 700 nm in Figure 2a indicative of a loss of electron absorption. Secondly, catalytically active holes that absorb at 500 nm have been shown to oxidise water on slower timescales, thereby indicating that this absorption arises from holes localised within the depletion layer.…”
supporting
confidence: 59%
“…[14][15] These defects manifest as reduced tungsten centres neighbouring sites absent in oxygen, and thus give rise to a characteristic broad W 5+ absorption at red wavelengths, rising into the near IR. [16][17] There is ongoing discussion in the literature regarding the effects of these states on charge transport and catalysis, with proponents claiming improved conductivity and critics proposing increased trap-mediated recombination. [18][19][20][21][22][23] These states lie energetically below the conduction band edge, with a fairly large energetic distribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the NiFe(OH) x modified homojunction, the bleach amplitude at 580 nm decreases dramatically relative to the bare homojunction photoanode, which suggests the large decrease of trapped photoelectrons by passivation of surface electron trap states 54 . On the other hand, the absorption amplitude at 694.3 nm also slightly decreases and the half-lifetime decreases to 0.19 ms due to the reduction of electron trap states, resulting from the increase of direct recombination 55 or the charge transfer from homojunction to NiFe(OH) x 56 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that for a ratio smaller than 2.00, the surface presents oxygen vacancies 50 . The presence of oxygen vacancies generates defects able to act as a trap for holes 51 . In consequence, the holes and excited electrons recombination is limited, implying an improved charge transfer.…”
mentioning
confidence: 99%